Basis Teologis-Filosofis Moderasi Pendidikan Agama Islam di Indonesia - Abdul Rozak Ali Maftuhin; Faridi Faridi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to explain the concept of religious moderation, examine its implementation within the context of Islamic Religious Education, and identify examples of religious moderation practices in Indonesia. The research employs a phenomenological method and is categorized as a literature study, utilizing secondary data from various documents. Data collection was conducted online, and data analysis followed an interactive model. The findings reveal that religious moderation is a perspective on religiosity that emphasizes tolerance. The main principle of moderation is the pursuit of balance, marked by a tolerant attitude. In Islamic education, religious moderation is interpreted as a moderate Islamic educational concept that focuses more on the quality of instruction. The Islamic teachings delivered emphasize beneficial and peaceful values. Therefore, promoting a moderate understanding of Islam in various educational institutions is essential. Religious moderation practices in Islamic education have been implemented across various institutions in Indonesia, both formal and non-formal, through training programs. Several elements applied include an inclusive curriculum, interfaith dialogue, respect for diversity, and efforts to prevent radicalism.